1996
DOI: 10.1086/310012
|View full text |Cite
|
Sign up to set email alerts
|

Parallax Observations with the [ITAL]Hubble Space Telescope[/ITAL] Yield the Distance to Geminga

Abstract: Using data from Hubble Space Telescope observations, we report the first optical measurement of the annual parallax of a neutron star. This is the counterpart of the X-ray/␥-ray pulsar Geminga, for which strong proper motion has already been reported. Significant displacement from such motion is detected using WFPC2 observations, taken at the dates of the maximum predicted parallactic factor. The resulting distance value is 157 pc (ϩ59, Ϫ34), just consistent with the lower end of the wide range derived from X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 14 publications
3
116
0
Order By: Relevance
“…All these objects related to prominent pulsars and to their associated multiwavelength counterparts. Two of them are nearby sources (Geminga with d = 160 pc, Caraveo et al 1996;and Vela with d = 290 pc, Caraveo et al 2001) and feature very extended VHE emission regions (Geminga ∼2.8 • , as indicated in Abdo et al 2007, and Vela X ∼0.5 • radius, as measured by H.E.S.S. ), as can be expected for close, extended objects.…”
Section: Leptonic Scenario: Pwnmentioning
confidence: 83%
“…All these objects related to prominent pulsars and to their associated multiwavelength counterparts. Two of them are nearby sources (Geminga with d = 160 pc, Caraveo et al 1996;and Vela with d = 290 pc, Caraveo et al 2001) and feature very extended VHE emission regions (Geminga ∼2.8 • , as indicated in Abdo et al 2007, and Vela X ∼0.5 • radius, as measured by H.E.S.S. ), as can be expected for close, extended objects.…”
Section: Leptonic Scenario: Pwnmentioning
confidence: 83%
“…Among this set of candidate sources we found that only the Monogem (PSR B0656+14) at a distance of d = 290 pc and age T = 1.1 × 10 5 years (Manchester et al 2005), and the Geminga pulsar (PSR J0633+1746) with d = 160 pc and T = 3.7 × 10 5 years (Caraveo et al 1996 [48]) give a significant contribution to the high energy electron and positron flux reaching the Earth. The observed spin-down luminosities of these pulsars areĖ PSD ≃ 3.8 × 10 34 erg s −1 andĖ PSD ≃ 3.2 × 10 34 erg s −1 respectively.…”
Section: Pulsar Interpretationmentioning
confidence: 90%
“…Following a robust method successfully applied in several previous astrometric works (see e.g. Caraveo et al 1996;Caraveo & Mignani 1999;Mignani et al , 2001Caraveo et al 2001), this relies on an accurate image superposition which is obtained by optimizing a linear coordinate transformation between two reference grids determined by a set of common reference objects.…”
Section: The Data Analysismentioning
confidence: 99%